Comparative clinical and laboratory study of rivaroxaban and its generic forms in patients with stable coronary artery disease - N. V. Lomakin; I. Yu. Tkach; E. A. Shirokov (Российский кардиологический журнал, 2025)
The course and complications of coronary artery disease (CAD) are associated with atherosclerosis progression and a high probability of atherothrombosis. Antithrombotic therapy is the most effective strategy for preventing cardiovascular events in atherosclerotic diseases. In accordance with current clinical guidelines for the prevention of myocardial infarction and stroke, all patients with stable CAD are recommended to take acetylsalicylic acid (ASA). In patients with a high risk of ischemic events without a high risk of bleeding, addition of low dose anticoagulant rivaroxaban to ASA is possible. The article discusses the design of a clinical and laboratory prospective single-center comparative study, the purpose of which is to compare the efficacy and safety of two following bioequivalent agents: the original (Xarelto, AO Bayer, Germany) and generic (Kruoksaban, OOO Ozon LLC, Russia) rivaroxaban.